The Influence of The Meaning of Work on Affective Organizational Commitment With Work Engagement as A Mediator for Employees of PT X Makassar Region - Mutmainnah, Mutmainnah; Tamar, Muhammad; Wirawan, Hillman (Universitas Pamulang, 2024)
This research aims to examine the influence of the meaning of work on affective organizational commitment with work engagement acting as a mediating variable for employees of PT X Makassar Region. The number of samples in this study was 247 people. This research examines the indirect effect of work meaning on affective organizational commitment through the mediating role of work engagement. The analysis technique used is multiple regression test with bootstrapping technique and Sobel test. The results of this research show that the meaning of work influences work engagement and influences affective organizational commitment directly. Thus, it can be concluded that work engagement partially mediates.